Recommendations for Clinical Decision-making in Children with Type 1 Diabetes and Celiac Disease: Type 1 Diabetes and Celiac Disease Joint Working Group Report - Hatun, Sukru; Dalgic, Buket; Goksen, Damla; Aydogdu, Sema; Erdeve, Senay Savas; Kulogu, Zarife; Selimoglu, Mukadder Ayse (Galenos Publ House, 2022)
It is well-known that in children with type 1 diabetes (T1D), the frequency of Celiac disease (CD) is increased due to mechanisms which are not fully elucidated but include autoimmune injury as well as shared genetic predisposition. Although histopathologic examination is the gold standard for diagnosis, avoiding unnecessary endoscopy is crucial. Therefore, for both clinicians and patients' families, the diagnosis of CD remains challenging. In light of this, a joint working group, the Type 1 Diabetes and Celiac Disease Joint Working Group, was convened, with the aim of reporting institutional data and reviewing current international guidelines, in order to provide a framework for clinicians. Several controversial issues were discussed: For CD screening in children with T1D, regardless of age, it is recommended to measure tissue transglutaminase-immunoglobulin A (tTG-IgA) and/or endomysial-IgA antibody due to their high sensitivity and specificity. However, the decision-making process based on tTG-IgA titer in children with T1D is still debated, since tTGIgA titers may fluctuate in children with T1D. Moreover, seronegativity may occur spontaneously. The authors' own data showed that most of the cases who have biopsy-proven CD had tTG-IgA levels 7-10 times above the upper limit. The decision for endoscopy based solely on tTG-IgA levels should be avoided, except in cases where tTG-IgA levels are seven times and above the upper limit. A closer collaboration should be built between divisions of pediatric endocrinology and gastroenterology in terms of screening, diagnosis and follow-up of children with T1D and suspicious CD.
Keywords: Children; type 1 diabetes; Celiac disease; anti-tissue transglutaminase-IgA